APLIKASI ALAT VACUM PROCESS PADA PENYADAPAN POHON KELAPA TERHADAP VOLUME NIRA YANG DIHASILKAN SEBAGAI UPAYA PENINGKATAN PRODUKTIVITAS PETANI GULA MERAH KABUPATEN BANYUWANGI - Anam Chairul; Kurniasanti Alief Sandryas; Muzaka Khairul (Jurusan Teknik Mesin Fakultas Teknik Universitas Jember, 2018)
Banyuwangi has the advantage of being a coastal area including abundant coconut trees. The problem in the tapping process of this sap, especially coconut trees, is the clogging of the tapping area on the flower stem that occurs naturally. So far what has been done is by cleaning the blockage through thin cuts on the tapped part. This is a tiring routine that must be carried out every morning and evening, plus the tapping roomie is brought manually then the shelter is taken up to be reassembled on tapped flower bunches. Therefore it is necessary to have the best solution to the problem. The method of this research is a vacuum system that is applied to the tapping process of the sapper with the aim of finding a comparison of the effect of manual and vacuum methods on the volume of sap produced on coconut trees and the results of fluid obtained compared. The results showed that the tapping process of coconut sap namely the manual method achieved an average yield of 24.12 liters in the morning and 23.15 liters in the afternoon and by using vacuum averaged 24.33 liters in the morning and 23.70 liters in the afternoon. Keywords: Tapping of coconut trees, vacuum system, the volume of sap